(untitled) (New York, 2006)
This comprehensive collection of 205 scores illustrates every significant trend and genre of Western music from antiquity to modern times. Highlights of the repertoire include new works from all periods: more contrasting virelais, ballades, and other chansons from the fourteenth through the sixteenth centuries; large-scale choral works, including Gabrieli’s In ecclesiis, Lully’s Te Deum, Haydn’s Creation, and Prokofiev’s Alexander Nevsky; more opera, including Norma, Les Huguenots, and Madama Butterfly; orchestral and chamber works by Schubert, Schumann, Brahms, Dvorák, and Tchaikovsky; and new twentieth-century works by Satie, Bartók, Milhaud, Prokofiev, Varèse, Hindemith, Cowell, Cage, Feldman, Stockhausen, Boulez, Berio, Reich, Adams, Ligeti, Schnittke, and Michael Daugherty.
Keywords: Musical analysis,Music appreciation,Phân tích âm nhạc,Sự đánh giá âm nhạc